Effect of laser-textured surface of Ti6Al4V on frictional wear behavior - Zul, M. H.; Ishak, M.; Nasir, R. M.; Aiman, M. H.; Quazi, M. M. (Universiti Malaysia Pahang, 2023)
The need for titanium and its alloys has led to a significant increase in commercial manufacturing, although this material’s poor tribological qualities have been a drawback. The present study was to determine the effect of laser-textured surfaces to enhance Ti6Al4V surface wear performance. The sample underwent laser texturing based on pre-set parameter values at 15 W power at a laser scanning speed of 200 mm/s with a frequency of 50 kHz. The surface morphological and topological profile of laser-textured Ti6Al4V was characterized with also the surface microhardness. A comparative appraisal of wear rate (WR) and coefficient of friction (COF) for related samples of as-received Ti6Al4V and laser-textured Ti6Al4V was performed under dry and oil sliding conditions. The results revealed that the formation of oxidation due to the frictional force and plastic displacement plays a role of abrasive to the laser-textured surface and may result in increasing the COF. The wear rate of the laser-textured surface of Ti6Al4V exhibited 88.31% improvement compared to the as-received Ti6Al4V in the dry sliding wear test. It was proved that Ti6Al4V could benefit from LST to gain effectively enhanced wear performance.